Gradual correction of phosphorus availability in the no-tillage system - KURIHARA, CARLOS HISSAO; SILVA, WILLIAM MARRA; Dias, Matheus Marques; Tsujigushi, Bruno Patrício; Silva, João Vitor de Souza (Revista Ceres, 2016)
In areas cultivated under no-tillage system, the availability of phosphorus (P) can be raised by means of the gradual corrective fertilization, applying phosphorus into sowing furrows at doses higher than those required by the crops. The objective of this work was to establish the amount of P to be applied in soybean crop to increase content of P to preestablished values at the depth of 0.0 to 0.10 m. An experiment was carried out on a clayey Haplorthox soil with a randomized block experimental design distributed in split-split plot, with four replications. Two soybean crop systems (single or intercropped with Panicum maximum Jacq cv. Aruana) were evaluated in the plots. In addition, it was evaluated four P levels (0, 60, 120 and 180 kg ha-1 P2O5) applied in the first year in the split plots; and four P levels (0, 30, 60 and 90 kg ha-1 P2O5) applied in the two subsequent crops in the split-split plot. Contents of P were extracted by Mehlich-1 and Anion Exchange Resin methods from soil samples collected in the split-split plot. It was found that it is necessary to apply 19.4 or 11.1 kg ha-1 of P2O5, via triple superphosphate as source, to increase 1 mg dm-3 of P extracted by Mehlich-1 or Resin, respectively, in the 0.0 to 0.10 m layer of depth. The soil drain P character decreases as the amount of this nutrient supplied in the previous crops is increased.